Fair Restrained Dominating Set in the Corona of Graphs - Debie Honey P. Galleros; Enrico L. Enriquez (International Journal of Engineering and Management Research, 2020)
In this paper, we give the characterization of a fair restrained dominating set in the corona of two nontrivial connected graphs and give some important results.